Hippocampal atrophy is independent of amyloid status 3 years after ischemic stroke: Neuroimaging / multi‐modal comparisons. (7th December 2020) - Brodtmann, Amy; Khlif, Mohamed Salah; Bird, Laura J.; Churilov, Leonid; Cumming, Toby; Werden, Emilio
Abstract: Background: Hippocampal atrophy, long thought to be an imaging signature of Alzheimer's disease, is seen in a range of neurodegenerative disorders, and in association with vascular risk factors in people without dementia. We examined hippocampal volume (HV) in a group of ischemic stroke patients who participated in an amyloid PET imaging study 3 years after their stroke. Given the complex interactions between normal brain aging, vascular risk factors and brain histopathology, we hypothesized that there would be no association between HV and amyloid status. Method: The Cognition And Neocortical Volume After Stroke (CANVAS) study is an observational cohort study of 135 patients with ischemic stroke examining brain volume and cognition over 3 years compared to healthy controls. Amyloid 18 F‐NAV4694 PET imaging was offered at 3 years as a sub‐study. Only participants with usable MRI scans at 3 years were included. We report centiloids (CLs) not SUVRs for comparison of our results with others using different amyloid PET tracers. CL amyloid status was classified as: CL<15 NEGATIVE; CL 15‐25 UNCERTAIN; CL>25 POSITIVE. In addition, Brain Banking was offered to all CANVAS participants: participants are classified amyloid‐positive with Braak staging>3. We compared HVs between the amyloid‐positive and ‐negative groups and associations between co‐morbidities and vascular risk factors (VRFs) by comparing Charlson Co‐morbidity Indices (CCI) and number of VRF using Multiway ANOVA ( anovan, MATLAB 2019b). Result: One participant was Brain Banked; 34 (27 men) participated in the PET imaging sub‐study. There were no differences in years of education, VRF and CCI between PET and non‐PET participants, although PET participants had larger heads (Fig1). CCI was significantly associated with HV (p<0.0001) but CCI variability was explained by age (collinear). VRFs were not significantly associated with HV. PET participants were significantly older than the 61 (42 men) non‐PET participants (69.6+/‐8.6 vs 64.2+/‐13.5 years; p=0.037). Five participants were amyloid‐positive: Brain Bank participant (Braak Stage 5), 4 PET participants (Fig2). There was no association between amyloid CLs and HV, but amyloid positivity was associated with greater CCI. Conclusion: In this small study of stroke patients, hippocampal atrophy occurred independently of amyloid pathology and was more associated with age and co‐morbidity.